Stability of the zootechnical additives SUBTILPROBIO® C-31, C-34 and E-44 under different temperature conditions - Milián, Grethel; Rondón, Ana j.; Pérez, M. L.; Martínez, Yordanys; Bocourt, R.; Rodríguez, Marlén; Beruvides, A.; Portilla, Yadileiny (Cuban Journal of Agricultural Science, 2019)
In intensive livestock production, not all storage conditions are available for the conservation of biological products. Hence, the objective of this research was to verify the stability of three zootechnical additives: SUBTILPROBIO® C-31, C-34 and E-44 at room temperature (24 ± 3 ºC) and in refrigeration (4 ± 8 ºC). For this, three experiments were carried out: 1) microbiological quality of the additives, 2) viability of the endospores and 3) pH dynamics. The results revealed the absence of contaminating microorganisms in the additives, such as fecal and total coliforms, Pseudomonas auruginosa, Staphylococcus aureus, Bacillus cereus, Salmonella. The count of yeasts (<103mL) and fungi (<10CFU.mL-1), acceptable for products of animal consumption. The viability of endospores showed no difference in both temperatures (16 Log CFU.mL-1). However, the pH showed differences (P <0.05) between the initial hour and the seventh day for both temperatures [environment: C-31: 6.38 / 5.70; C-34: 6.38 / 5.74; E-44: 6.38 / 5.77 and refrigeration: C-31: 6.38 / 4.52; C-34: 6.38 / 4.50; E-44: 6.38 / 4.49]. It can concluded that there is no difference for both temperatures, which makes viable the preservation of zootechnical additives SUBTILPROBIO® C-31, C-34 and E-44 in both conditions. Key words: conservation of biological products, Bacillus subtilis, viability of endospores